KONTRIBUSI HASIL PENELITIAN ARKEOLOGI DALAM PROGRAM KEBHINEKAAN SEBAGAI PEMERSATU BANGSA: STUDI KASUS PADA SITUS KUBUR PRASEJARAH DI PANTAI UTARA JAWA TENGAH - Gunadi Kasnowihardjo (Berkala Arkeologi, 2016)
Lately, the decline in the understanding of Pancasila and Bhinneka Tunggal Ika as the identity and ideology of the Indonesian nation has become a central issue that we must solve together. Diversity in ethnicity, religion, race, and customs owned by the Indonesian nation has been perceived and understood since thousands of years ago, diversities which were starting to be joined together during the Majapahit era. Mpu Tantular in his infamous Kakawin Sutasoma has written â€œbhinnekatunggalikatan hanadharma mangrwaâ€, an idea about unity in diversity. From then on, this idea has grown into nationalism spirit, which eventually became a tremendous force to repel the Dutch colonialist. Therefore these diversities must be maintained and preserved. Through a study about the past, archaeology has a role in protecting and preserving the cultural diversity to unify the nation.